Changes in Transcriptome-Associated Co-Expression Profile of Embryonic External Ear Development After Prkra Gene Mutation. Issue 2 (29th March 2023) - Liu, Wei; Lin, Lin; Yang, Qinghua; Jin, Shengyang; Jiang, Haiyue
Abstract : The aim was to understand the changes in gene expression during the mouse external ear embryonic development in the full transcriptomes of mice with a point mutation in the Prkra gene, the outer ear tissues of mouse embryos were developed to embryonic day (E)15.5 and E17.5, and a Prkra Little-ear mouse model was obtained. The purpose of this study was to perform a whole transcriptome association analysis of the Prkra Little-ear mouse model during external ear embryonic development using advanced sequencing techniques. The association analysis of the full transcriptome mainly included lncRNA and mRNA association analysis, lncRNA and miRNA association analysis, miRNA and mRNA association analysis, circRNA and mRNA association analysis, circRNA, miRNA, and mRNA association analysis, and lncRNA, miRNA, and mRNA association analysis. The results of the correlation analysis showed that in the Prkra Little-ear mouse embryo development of the external ear was regulated by whole transcriptome and that these changes were different in wild-type mice. This study provides a new concept for elucidating the mechanism of the regulation of mouse external ear development.